THE ROLE OF ORGANIZATIONAL AND ECONOMIC MECHANISM OF STRATEGIC COMPANY MANAGEMENT IN THE NATIONAL ECONOMY - О. Parfentieva; А. Grechan; A. Bezuglyi; К. Kompanets; О. Salimon (Фінансово-кредитна діяльність: проблеми теорії та практики, 2022)
Abstract. The COVID-19 pandemic caused an economic downturn, and business development strategies based on globalization and integration failed. So it is necessary to develop new organizational and economic mechanisms of strategic company management, which will compensate for the losses of foreign markets. The focus should be on operation within the national economy as a major alternative to globalised markets. The purpose was to develop proposals for improving the mechanism of strategic company management in the context of implementation of investment policy. The study involved scientific developments that consider the theoretical and practical aspects of development, analysis and implementation of dynamic models of company management. The study showed that the main purpose of strategic company management is to maximize its value to shareholders. The methodological framework of the study is systems theory, a systems approach to strategic company management, theory and practice of simulation. The mechanism of strategic company management based on investment activity is suggested. An algorithm for improving strategic investment management is suggested. The mechanism allows the management to identify and analyze possible consequences in implementation of investment strategies, as well as take into account the impact of these factors on the stable company operation. The proposed mechanism of strategic management also allows linking the full range of strategic actions, strategic marketing research, company’s investment policy, measures to control, identify and take into account the degree of risk, evaluate strategies and adjust management decisions to ensure company’s sustainable development.